2004
DOI: 10.1007/bf03018432
|View full text |Cite
|
Sign up to set email alerts
|

Une perfusion de morphine améliore l’analgésie autocontrôlée après cardiochirurgie

Abstract: Morphine PCA effectively controlled postoperative pain after cardiac surgery. The addition of a background infusion of morphine enhanced analgesia and increased morphine consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 22 publications
(44 reference statements)
2
23
0
2
Order By: Relevance
“…However, morphine consumption and possible side effects as reported by other studies [6,12,13,16] can help clinicians to choose the best alternative.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, morphine consumption and possible side effects as reported by other studies [6,12,13,16] can help clinicians to choose the best alternative.…”
Section: Discussionmentioning
confidence: 97%
“…However, another study involving morphine basal infusion enrolled 35 patients and was unable to show any significant difference in pain management when compared to PCA alone [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study design of mixed paired and unpaired observations decreases uneven distribution of unknown confounders. Although our study is of comparable size as other trials with PCA [9][10][11][12][13][14][15][16][17][18][19][20], a larger trial will be needed to demonstrate whether the use of PCA in vaso-occlusive crisis will result in a reduction in length of hospital stay and complications such as acute chest syndrome. Second, the PCA design of our study made a complete blinding of the study impossible and could therefore be subject to bias.…”
Section: Side Effects and Adverse Eventsmentioning
confidence: 94%
“…A possible explanation for this effect, which also could explain the low morphine consumption in the PCA-treated patients in the present study, may be that a more rapid analgesic effect is induced by bolus administration of morphine rather than CI. However, comparative trials with PCA in patients with other causes of pain have demonstrated conflicting results on the cumulative morphine consumption [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Side Effects and Adverse Eventsmentioning
confidence: 99%
“…Some studies comparing the two types of patient-controlled analgesia (PCA) suggest that users of continuous PCA infusion of morphine have similar postoperative pain intensity but consume more morphine and have a greater incidence of adverse effects [4][5][6][7][8]. However, one study reported better postoperative analgesia [9]. Due to the inconsistency of results and the continued wide use of PCA, we performed a prospective, randomized study to evaluate the effectiveness of pain management and occurrence of side effects in two groups of women who underwent abdominal hysterectomies: one group receiving self-administered PCA only (PCA) and the other receiving continuous PCA with the ability to add extra doses if needed (continuous PCA).…”
Section: Introductionmentioning
confidence: 99%